Climate Change Leads to a Reduction in Symbiotic Derived Cnidarian Biodiversity on Coral Reefs - Goulet, Tamar L.; Goulet, Denis (Frontiers in Ecology and Evolution, 2021)
Symbiotic relationships enable partners to thrive and survive in habitats where they would either not be as successful, or potentially not exist, without the symbiosis. The coral reef ecosystem, and its immense biodiversity, relies on the symbioses between cnidarians (e.g. scleractinian corals, octocorals, sea anemones, jellyfish) and multiple organisms including dinoflagellate algae (family Symbiodiniaceae), bivalves, crabs, shrimps, and fishes. In this review, we discuss the ramifications of whether coral reef cnidarian symbioses are obligatory, whereby at least one of the partners must be in the symbiosis in order to survive or are facultative. Furthermore, we cover the consequences of cnidarian symbioses exhibiting partner flexibility or fidelity. Fidelity, where a symbiotic partner can only engage in symbiosis with a subset of partners, may be absolute or context dependent. Current literature demonstrates that many cnidarian symbioses are highly obligative and appear to exhibit absolute fidelity. Consequently, for many coral reef cnidarian symbioses, surviving changing environmental conditions will depend on the robustness and potential plasticity of the existing host-symbiont(s) combination. If environmental conditions detrimentally affect even one component of this symbiotic consortium, it may lead to a cascade effect and the collapse of the entire symbiosis. Symbiosis is at the heart of the coral reef ecosystem, its existence, and its high biodiversity. Climate change may cause the demise of some of the cnidarian symbioses, leading to subsequent reduction in biodiversity on coral reefs.